Luxury marketing and brand strategy : theory and practice for a changing world - Olšanová, Květa; Cook, Gina, 1970-; Zlatić, Marija (Abingdon, Oxon ; New York, NY : Routledge, 2026)
"This text provides a comprehensive and strategic overview of luxury marketing and brand management, guiding brands to balance tradition with innovation as they navigate modern challenges and seize opportunities in a rapidly evolving global market. The book explores the core aspects of luxury branding, including the defining traits of luxury brands, the dominance of major luxury groups, and the resilience of independent brands with storied histories. It explores the delicate balance required to maintain a brand's luxury status amidst evolving consumer expectations, technological advancements, and sustainability concerns. Students will gain insight into innovative marketing strategies, from the use of NFTs and blockchain to the integration of AI and the metaverse in enhancing customer experiences. Offering a clear and engaging pathway through the complexities of luxury brand management, the authors draw on their extensive academic and professional experience, presenting a rich blend of theoretical insights and real-world global and cross-industry case studies from prestigious brands like Cartier, Van Cleef & Arpels, Chanel, Ferrari, Orient-Express and many others. This textbook is designed to be the cornerstone for advanced undergraduate and postgraduate courses in Luxury Marketing and Luxury Brand Management. With a focus on the latest trends and future directions in luxury marketing, Luxury Marketing and Brand Strategy is not only an academic resource but also a practical guide for navigating and succeeding in the dynamic luxury market. Online resources include PowerPoint lecture slides and a test bank"-- Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Luxury goods industry -- Marketing; Selling -- Luxuries